Construction and Validation of Research Satisfaction Scale (RSS) for Post-Research Analysis of Graduates (Indian Journal of Extension Education, 2024)
A better understanding of the researcher’s attitude starts with knowing their satisfaction level, which helps the agricultural universities understand research graduates and make necessary improvement plans. Absence of such a specific scale, forced to draft present piece in 2022 focusing on developing the Research Satisfaction Scale using the scale product method. Initially, 63 items were pooled, scrutinized, and reduced to 57 based on the rules of Edward and Kilpatrick and segregated into three groups as: ‘Before, while performing, and after performing research.’ Scale and Quartile values were calculated, and the statements with an S-value less than the Q-value were eliminated, bringing the number of statements to 53. For validation – Content Validity Index (CVI), both item and scale were used and Cronbach’s alpha for measuring reliability. The score of Item- CVI <0.70 were eliminated, making the total number of statements 36. The Scale – CVI was 0.92, with an internal consistency value of 0.792, making the developed scale with 36 items valid and reliable. Research studies can be formulated by ICAR and SAUs to understand the contentment the graduates attained with their undertaken research activity.